Fundamental Analysis of Syari’ah Stock In Jakarta Islamic Index - Ningrum, Oktavima (International Publisher (YAPENBI), 2022)
This study aims to determine the growth prospects and fair value of a stock by using fundamental analysis with the EPS (Earning Per Share) and PER (Price To Earning Ratio) methods and price book value determines the investment. The research method used is to use a descriptive method with a qualitative approach from the Annual Financial Reports of 15 Islamic companies that are consistent in the Jakarta Islamic index . The results of this study are Islamic companies in JII have experienced quite rapid growth despite the Covid 19 incident in 2020 but still generate income. The best EPS rating of 15 Syari’ah companies in 2020 in the second quarter is UNTR of 899.51 while the lowest PER level is KLBF of 5.85x. However, if viewed from the market capitalization and the number of shares outstanding, the fair value of KLBF. For Income Ratio to PBV (Price Book Value) results in a decision to sell the stock price.